2013
DOI: 10.1186/1743-422x-10-309
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from Acacia catechu suppress HIV-1 replication by inhibiting the activities of the viral protease and Tat

Abstract: BackgroundAcacia catechu (Mimosa family) stem bark extracts have been used traditionally as a dietary supplement as well as a folk medicine given its reported anti-inflammatory, immunomodulatory, hepatoprotective, antioxidant, anti-microbial and anti-tumor activities. The present study was undertaken to evaluate the anti-HIV-1 activity of the extracts from stem bark of A. catechu.MethodsThe aqueous and 50% ethanolic extracts of A. catechu stem bark were prepared and 50% ethanolic extract was further fractioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…The mechanism of action of A. arabica is known. It specifically inhibits the stage of viral intracellular multiplication [ 149 , 167 , 168 , 169 ]. Furthermore, A. arabica contains several bioactive components extracted from the leaves of the plant which are responsible for its bioactivity, such as flavonoids, methyl 3,4,5 tri hydroxyl benzoate, p -coumaroyl glucoside, p -coumaroylquinic acid, ferulic acid, isoferulic acid, epicatechin-3-gallate, ascorbic acid, quercetin 3-O-(4′-O-acetyl)-rhamnopyranoside, oleic acid, myristic acid, palmitic acid and steroidal sapogenin aglycone [ 166 , 167 , 168 , 276 ].…”
Section: Other Medicinal Plants In Use Against Various Viral Infecmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of action of A. arabica is known. It specifically inhibits the stage of viral intracellular multiplication [ 149 , 167 , 168 , 169 ]. Furthermore, A. arabica contains several bioactive components extracted from the leaves of the plant which are responsible for its bioactivity, such as flavonoids, methyl 3,4,5 tri hydroxyl benzoate, p -coumaroyl glucoside, p -coumaroylquinic acid, ferulic acid, isoferulic acid, epicatechin-3-gallate, ascorbic acid, quercetin 3-O-(4′-O-acetyl)-rhamnopyranoside, oleic acid, myristic acid, palmitic acid and steroidal sapogenin aglycone [ 166 , 167 , 168 , 276 ].…”
Section: Other Medicinal Plants In Use Against Various Viral Infecmentioning
confidence: 99%
“…Furthermore, A. arabica contains several bioactive components extracted from the leaves of the plant which are responsible for its bioactivity, such as flavonoids, methyl 3,4,5 tri hydroxyl benzoate, p -coumaroyl glucoside, p -coumaroylquinic acid, ferulic acid, isoferulic acid, epicatechin-3-gallate, ascorbic acid, quercetin 3-O-(4′-O-acetyl)-rhamnopyranoside, oleic acid, myristic acid, palmitic acid and steroidal sapogenin aglycone [ 166 , 167 , 168 , 276 ]. A. arabica also has the potential to inhibit the viral replication against HIV infection [ 149 , 169 ]. Due to its antiviral nature, it is highly recommended to use A. arabica for controlling/managing SARS-CoV-2 infection.…”
Section: Other Medicinal Plants In Use Against Various Viral Infecmentioning
confidence: 99%
“…Reports indicated that a standardized extracts produced from Acacia catechu bark extracts contain catechin, kaempferol, rutin, ferulic acid, and caeffic acid. 13 The extract is claimed to possess all the active principles of the plant. The extract was used in the present study after preliminary in vitro tests.…”
Section: Plant Extractmentioning
confidence: 99%
“…8 It also showed anti-lipid peroxidative and superoxide anion scavenging activity 12 Many therapeutic compounds such as catechin, kaempferol, rutin, ferulic acid and caeffic acid have been isolated from the bark of Acacia catechu. 13 The methanolic extract of Acacia catechu possesses antimicrobial potential against many microorganisms and anti-genotoxicity power. 11,14 To best of our knowledge, no work has been done on the efficacy of MEBA against lungs toxicity.…”
mentioning
confidence: 99%
“…Acacia catechu (Mimosa family) extracts and Mori folium, the leaves of Morus alba L., have been traditionally used as a dietary supplement or folk medicine due to the documented anti-inflammatory activity, as well as protection of the liver and hypertension, respectively [122]. The aqueous extract of Acacia catechu heartwood is a good source of catechin and epicatechin, with smaller quantities of flavonoids, which have well-documented health benefits [123], also in the context of OA as it has been observed in this review.…”
Section: Acacia Catechu and Mori Folium Standardized Blend (Ub1306)mentioning
confidence: 99%